2008
DOI: 10.15288/jsad.2008.69.649
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Domain Predictors of Problematic Alcohol Use in Young Adulthood

Abstract: ABSTRACT. Objective: The goal of this study was to identify predictors of problematic young adult alcohol use. Method: The sample consisted of 141 subjects (81 females) participating in a national study of genetic risk factors for alcoholism. All subjects were evaluated fi rst as children or adolescents, then approximately 5 years later as young adults. Outcome consisted of the number of alcohol symptoms (0-10) endorsed at this second time point. Predictors of outcome were drawn from fi ve domains representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 69 publications
2
18
0
1
Order By: Relevance
“…It would be interesting to evaluate whether the candidate genes (e.g. GABRA2 [48] , CHRM2 [49] and MAOA [50] ) that have been implicated in familial risk for externalizing disorders might play a role in affecting both cognitive control and BMI in adolescents. A future study will examine this question.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to evaluate whether the candidate genes (e.g. GABRA2 [48] , CHRM2 [49] and MAOA [50] ) that have been implicated in familial risk for externalizing disorders might play a role in affecting both cognitive control and BMI in adolescents. A future study will examine this question.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a consistent elevation in the risk for alcohol dependence associated with GABRA2 is not apparent until the mid-20s and then remains constant throughout adulthood (Dick, et al, 2006b; Kramer, et al, 2008). A gene-environment correlation and a gene-environment interaction associated with GABRA2 , marital status and alcohol dependence have been reported, suggesting that GABRA2 interacts with environmental factors and life style in determining the risk for alcohol dependence (Dick, et al, 2006a).…”
Section: Gabra2 and Alcohol Dependencementioning
confidence: 99%
“…COGA has used a variety of strategies to aid in gene identifi cation, including the use of rich phenotyping to characterize genetic effects (Dick et al, 2013b;Kramer et al, 2008), as well as electrophysiological endophenotypes (Begleiter & Porjesz, 1999;Dick et al, 2006b). In addition, the study has used a variety of genetic designs and methodologies.…”
mentioning
confidence: 99%